Pengaruh Media Edukasi terhadap Peningkatan Pengetahuan Pencegahan Diabetes Mellitus pada Remaja - Wina Fitriyani; Ratih Kurniasari (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2022)
Diabetes is a metabolic disease characterized by hyperglycemia or high blood sugar caused by impaired insulin secretion and insulin resistance. The increasing number of diabetes mellitus can be caused by a lack of knowledge about the disease. Changes in knowledge can be done by providing education through print media or application media. The purpose of this study was to determine the effect of providing education about diabetes through leaflets and websites. This type of research is a quasi-experimental design with a pretest-posttest design. The research sample was 40 respondents with an age range of 15-18 years with 2 intervention groups receiving education through leaflets and websites. The results of the Wilcoxon test on leaflet media get a p value of 0.001 which provides education that has an effect on increasing knowledge of diabetes mellitus in adolescents. Then on the media site, the results of the paired t test obtained a p value of 0.000 which provides education with a significant effect on increasing knowledge of diabetes mellitus in adolescents. The conclusion of this research is that leaflet and website media have a significant influence on increasing knowledge of diabetes mellitus in adolescents.